MANAJEMEN INOVASI PENGELOLAAN DANA HAJI DAN OPTIMALISASI INVESTASI EMAS - Andriani, Sri; Sismanto, Sismanto; Siswanto, Siswanto; Djalaluddin, Ahmad; Rikza, Abdullah (Ekonomi Syariah STAI Sangatta Kutai Timur, 2024)
Hajj, the fifth pillar of Islam, holds great importance and draws immense interest from Indonesian Muslims. Despite limited quotas, the number of prospective pilgrims continues to rise annually, posing challenges in managing hajj funds overseen by the Hajj Financial Management Agency (BPKH). This study explores innovative approaches to hajj fund management, focusing on optimizing investments, particularly in gold, a stable and secure Islamic financial instrument. The study analyzes literature and regulations on hajj financial management using a qualitative library research method. The findings indicate that BPKH’s fund management, based on Islamic principles, has improved significantly. Diversification through sukuk, cash waqf, and gold has helped secure hajj funds, though gold price volatility remains a challenge. Gold investments provide a hedge against inflation and market volatility, especially during economic crises. The study highlights the importance of innovative investment strategies to enhance the productivity and sustainability of hajj funds, with a recommendation for further portfolio diversification to maximize economic benefits for Indonesia’s Muslim population.